Determination of Muscone in Rats Plasma following Oral Administration of Artificial Musk: Using of Combined Headspace Gas Chromatography-Mass Spectrometry - Qibiao Wu; Haitao Li; Yujing Leng; Haishan Deng; Haibo Cheng; Weixing Shen (Journal of Spectroscopy)
To develop an analytical method for determination of plasma concentrations of muscone in rats following oral administration of artificial musk, with the aim of investigating the pharmacokinetic profile of artificial musk. Plasma samples were pretreated with acetonitrile to precipitate proteins. Headspace injection coupled with gas chromatography-mass spectrometry was used for quantitative analysis of muscone concentrations. A strong linear relationship was obtained for plasma muscone concentrations ranging from 75.6 to 7560 ng·mL−1  R2=0.9998, with the minimum detectable concentration being 25 ng·mL−1. The within-day and interday precision for determination of three different concentrations of muscone were favorable (RSD < 25%). The average absolute recovery ranged from 83.7 to 88.6%, with an average relative recovery of 100.5 to 109.8%. The method described was characterized by stability and reliability, and in the present study showed significant specificity and high sensitivity. This method would be applicable to the analysis of plasma concentrations of muscone in preclinical contexts, where artificial musk is used.